Nature-based solutions for urban biodiversity governance. Issue 110 (August 2020) - Xie, Linjun; Bulkeley, Harriet
Highlights: European cities are making explicit contributions to biodiversity through nature-based solutions, using quantitative targets. The Post-2020 Global Biodiversity Framework should incorporate the goals of Conserve, Restore, and Thrive that cities pursue for biodiversity. Urban NBS need to further integrate biodiversity goals, as well as restoration actions that emphasize species and genetic diversity. Abstract: In this paper, we examine how cities are working with nature-based solutions for biodiversity. Drawing on a sample of 199 nature-based solutions across Europe, we identify how cities work with nature-based solutions to conserve nature, restore nature, and to find ways to thrive through harnessing nature's contribution to people. Our findings show that cities are making explicit contributions to biodiversity through nature-based solutions, and often adopt specific and quantifiable targets to guide their actions. Yet there is significant variation in the ways in which biodiversity goals and interventions are being pursued. Where biodiversity goals and actions are included in nature-based solutions, they are mainly ecosystem-based - focusing on the protection, restoration or enhancement of the integrity, functionality, and connectivity of habitats and ecosystems - with fewer focused on specific species, and very few projects concerned with genetic diversity. Although it is often assumed that urban action towards biodiversity goals will be undertaken through local planning processes, our analysis shows that European cities are taking project-based actions for biodiversity through a set of explicit, quantitative and measurable targets, which are tailored to the specific conditions of urban settings. On the basis of these findings, we suggest that if cities are to achieve ambitious goals for biodiversity over the next decade, new international frameworks being developed for the post-2020 period should include targets that acknowledge the way in which biodiversity is governed in cities and the contribution that cities make to conserve, restore and thrive with nature to guide urban action.